Forest carbon accounting methods and the consequences of forest bioenergy for national greenhouse gas emissions inventories - McKechnie, Jon; Colombo, Steve; MacLean, Heather L. (Elsevier, 2014)
While bioenergy plays a key role in strategies for increasing renewable energy deployment, studies assessing greenhouse gas (GHG) emissions from forest bioenergy systems have identified a potential trade-off of the system with forest carbon stocks. Of particular importance to national GHG inventories is how trade-offs between forest carbon stocks and bioenergy production are accounted for within the Agriculture, Forestry and Other Land Use (AFOLU) sector under current and future international climate change mitigation agreements. Through a case study of electricity produced using wood pellets from harvested forest stands in Ontario, Canada, this study assesses the implications of forest carbon accounting approaches on net emissions attributable to pellets produced for domestic use or export. Particular emphasis is placed on the Forest Management Reference Level (FMRL) method, as it will be employed by most Annex I nations in the next Kyoto Protocol Commitment Period. While bioenergy production is found to reduce forest carbon sequestration, under the FMRL approach this trade-off may not be accounted for and thus not incur an accountable AFOLU-related emission, provided that total forest harvest remains at or below that defined under the FMRL baseline. In contrast, accounting for forest carbon trade-offs associated with harvest for bioenergy results in an increase in net GHG emissions (AFOLU and life cycle emissions) lasting 37 or 90 years (if displacing coal or natural gas combined cycle generation, respectively). AFOLU emissions calculated using the Gross-Net approach are dominated by legacy effects of past management and natural disturbance, indicating near-term net forest carbon increase but longer-term reduction in forest carbon stocks. Export of wood pellets to EU markets does not greatly affect the total life cycle GHG emissions of wood pellets. However, pellet exporting countries risk creating a considerable GHG emissions burden, as they are responsible for AFOLU and bioenergy production emissions but do not receive credit for pellets displacing fossil fuel-related GHG emissions. Countries producing bioenergy from forest biomass, whether for domestic use or for export, should carefully consider potential implications of alternate forest carbon accounting methods to ensure that potential bioenergy pathways can contribute to GHG emissions reduction targets.